(untitled) (Iraqi Journal of Medical Sciences, 2018)
Background: The prevention of preterm birth is a major health care priority. Objective: To evaluate the efficacy of vaginal progesterone pessary in reducing the rate of preterm delivery and subsequent neonatal morbidity and mortality events in pregnant women with a short cervical length early in the 2nd trimester. Methods: Women with a singleton pregnancy without a history of preterm labor nor a history of second trimester miscarriage, underwent cervical length measurement at 14+0 to 15+6 weeks of gestation. Women found to have a cervical length less than 30 mm received vaginal progesterone pessary (400 mg per pessary) on daily basis, or no treatment. Primary outcome was preterm delivery rate before 37 weeks gestation. Secondary outcome includes neonatal morbidity and mortality events. Results: From the 7725 pregnant women screened between the period from April 2015 to January 2017, 613 were found to have a cervical length less than 30 mm and only 518 pregnant women met the inclusion criteria and agreed to participate in this study. However, only 492 were followed up till the time of delivery. From those 252 women administered 400 mg vaginal progesterone pessary once daily at night and the remaining 240 women did not receive any form of progesterone and served as control. There was a significant reduction in preterm delivery rate less than 37 weeks gestation among women receiving progesterone vaginal pessary compared to the control group 11 (4.4%) vs 38 (15.8%), p value < 0.001. Regarding neonatal outcome, there were significant reduction in the frequency of respiratory distress syndrome, low birth weight neonates and admissions to neonatal intensive care unit in women taking vaginal progesterone pessary compared to the control. While other neonatal morbidity and mortality events, incidence of neonatal congenital anomalies were not significantly different between the two groups. Conclusion: Vaginal progesterone pessaries in women with a cervical length less than 30 mm early in the second trimester are found to be effective in reducing the rate of preterm birth and some of the prematurity related morbidity events. Keywords: preterm labor, vaginal progesterone pessaries, short cervix, premature delivery Citation: Khazaali EAA. Vaginal progesterone pessary for preterm labor prevention in women with a short cervix early in the second trimester. Iraqi JMS. 2018; 16(2): 133-143. doi: 10.22578/IJMS.16.2.4